URGENSI DAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM NIAT - Ma'arif, M. Jauharul (At-Tuhfah : Jurnal Studi Keislaman, 2020)
Based on the many verses of the Qur'a>n and the H{adi>th concerning the intentions and management of the heart, we can conclude that these two things are very important. One should not be surprised if there are many scholars who compile books on the topic of special discussion about the two. Starting something with the intention of causing interest and focus on a charity that affects the readiness of the heart to do it. This readiness is important because the heart is a place where ikhla>s{ as the mouth of all worship is. With the heart ready it is expected that a ‘charity can be carried out to the maximum. The intention is not just a ritual of worship, but if worship is carried out with full appreciation, there will appear a lot of Islamic religious education values ​​obtained. Among them are submission and obedience to religious orders, obeying regulations, growing enthusiasm to achieve good goals, determination and enthusiasm towards goodness, patience and a strong willingness to do something good even though heavy and difficult, awareness to improve the quality of faith and devotion, concern for self and the environment, vigilance to avoid or deal with liver disease, discipline, wisdom, love and obedience to religious orders.